ANTI-FIBROTIC EFFECTS OF CYCLOPHOSPHAMIDE ON BLEOMYCIN-INDUCED EXPERIMENTAL SCLERODERMA - Ozgen, M.; Koca, S.; Ustundag, B.; Ozercan, I.; Dagli, F.; Isik, A. (Clinical & Exper Rheumatology, 2010)
[Abstract Not Available]